Obstacles to Native Education in Late Colonial Peru. - Ramírez, Susan Elizabeth (Ethnohistory, 2022)
This article focuses on educational initiatives, the negotiations and resistance these efforts generated, and the barriers to these efforts during late colonial times. After a brief overview of formal and informal instruction, two examples of efforts to establish schools, especially for Native boys and girls, are outlined before an analysis of the obstacles organizers faced in founding them. Efforts were uneven. The superficial enthusiasm of some was tempered by the resistance of others. Contemporary manuscript texts in the archives of Spain, provincial capitals of Peru, and Lima highlight attitudes toward education in the 1780s and again closer to the eve of independence.